Value added reporting: A case study of abans listed manufacturing company limited in SriLanka - Subramaniyam, A.; Nimalathasan, B. (My University, 2011)
A business enterprise specifically a company is a conscious, deliberate and purposeful creation for satisfying the domain of aspiration of the society at large. It is an independent and a separate legal entity. The survival stability and growth of such entity within society largely depend on the wealth created by it through the collective efforts of all the stakeholders-shareholders, providers of loan capital, employees and the government. All these stakeholders are the parties to whom the result of operations of business is communicated. Therefore, present study attempts to show how and to what extent the Value Added Statement (VAS) can supplement additional financial information to satisfy all the stakeholders of the enterprise. Further, in order to meet the objectives of the study, data were collected from secondary sources mainly from financial report of the selected company (i.e., ABANS Listed Manufacturing Company) which was published by Colombo Stock Exchange (CSE) in Sri Lanka. Hence, it is clear that ratios using Value Added (VA) indicate that the company little bit efficient in terms of utilization of materials.